The road ahead : conclusions and recommendations - Fernandez, Ana (2012)
This report was commissioned by the DG SANCO for giving insights to the Conference “Health and Migration in the EU: Better health for all in an inclusive society” to be held in Lisbon on the 27th and 28th of September, 2007, under the Portuguese Presidency of the EU Council.